Media Competencies in the Use of Social Media in Postgraduate Education Contexts: a Mixed-Method Study - Venegas Mejía, Valia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study analyses media competencies in the use of social networks by postgraduate students, using a mixed approach with a parallel convergent design. A structured questionnaire was administered and semi-structured interviews were conducted to assess six dimensions of media competencies. The results show a high level of performance in most dimensions, particularly communication and interaction in digital environments and digital citizenship, reflecting active and ethical online participation. In contrast, the dimensions related to the interpretation of media language and content production show less development, indicating that students tend more towards the consumption and dissemination of information than critical or creative authorship for academic or social purposes. The findings reveal an imbalance between functional participation and reflective production, raising the need for curricular innovation with media competencies as a central purpose and to establish teaching strategies to strengthen hybrid learning, conscious creation, and transformation engagement on digital platforms and social media.